Strategic Use of Women’s Language Features in Jennifer Parlamis’ TED Talk - Qutratu'ain, Dita Shafa; Latifah, Nur (Jurnal Pendidikan : Riset dan Konseptual, 2026)
Recent studies have shown that women's language features (WLF) increasingly function as rhetorical strategies in professional discourse rather than mere gender markers, yet research in globally mediated speaking contexts such as TED Talks remains limited. This study aims to examine the types of WLF used in Jennifer Parlamis' TED Talk entitled "Why Venting Doesn't Help You with Anger" and to analyze their pragmatic and rhetorical functions in professional public speaking. A descriptive qualitative approach was employed, with data analyzed using Lakoff's (1975) framework, further interpreted through Holmes (1995) and Coates (2015). The findings reveal that emphatic stress emerged as the dominant feature, functioning to reinforce key messages and strengthen persuasive impact, while lexical hedges served to maintain an approachable conversational tone rather than signal uncertainty. Overall, WLF in this talk operates not as markers of gendered communication, but as intentional rhetorical strategies that enhance clarity, credibility, and emotional engagement with a global audience.